2022
DOI: 10.1101/2022.03.01.22271735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the reactogenicity and immunogenicity of a reduced and standard booster dose of the mRNA COVID-19 vaccine in healthy adults after two doses of inactivated vaccine

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has been a serious healthcare problem worldwide since December 2019. The third dose of heterologous vaccine was recently approved by World Health Organization. The present study compared the reactogenicity and immunogenicity of the reduced and standard third booster dose of the BNT162b2 and mRNA-1273 vaccine in adults who previously received the two-dose CoronaVac vaccine. Results showed that headache, joint pain, and diarrhea were more frequent in the 15 μg-tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Recently, we reported the results of a third dose booster study in healthy adults previously primed with two doses of CoronaVac. Our finding showed that a third heterologous dose elicited a robust immune response against the Omicron variant (Assawakosri et al, 2022b, Kanokudom et al, 2022b). Moreover, a booster with BNT162b2 in CoronaVac-primed individuals improved vaccine effectiveness (VE) to 92.7% for protection against COVID-19 infection in Brazil (Cerqueira-Silva et al, 2022b).…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Recently, we reported the results of a third dose booster study in healthy adults previously primed with two doses of CoronaVac. Our finding showed that a third heterologous dose elicited a robust immune response against the Omicron variant (Assawakosri et al, 2022b, Kanokudom et al, 2022b). Moreover, a booster with BNT162b2 in CoronaVac-primed individuals improved vaccine effectiveness (VE) to 92.7% for protection against COVID-19 infection in Brazil (Cerqueira-Silva et al, 2022b).…”
Section: Introductionmentioning
confidence: 50%
“…The study protocol was described in our previous studies (Assawakosri et al, 2022b, Kanokudom et al, 2022b). Briefly, this study was a prospective cohort study of heterologous third-dose vaccination.…”
Section: Methodsmentioning
confidence: 99%
“…A fractional low dose of BNT162b as a booster dose has been studied in Thailand among adults who received a primary series of the CoronaVac vaccine [28]. The study was conducted among 222 healthy adults with a median age of 39.1 years who received twodose CoronaVac for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The enrolled participants self-reported reactogenicity using an electronic or paper questionnaire, starting on the day of vaccination and for 7 subsequent days (days 0-7). Local, systemic and adverse events (AE) were classified as mild, moderate and severe, as previously described (Kanokudom et al, 2022a).…”
Section: Safety Assessmentsmentioning
confidence: 99%